2018
DOI: 10.21873/anticanres.12563
|View full text |Cite
|
Sign up to set email alerts
|

Liver-dominant Breast Cancer Metastasis: A Comparative Outcomes Study of Chemoembolization Versus Radioembolization

Abstract: TARE is better tolerated than TACE for the treatment of liver-dominant breast cancer metastasis. There was a trend towards improved survival with TARE; however, it did not approach statistical significance. Larger studies are needed to validate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Thirdly, TACE and TARE were deemed as one kind of therapy in this study to establish a network, since no significant difference was reported between TACE and TARE. [23,45] Consequently, findings of the current network meta-analysis might not completely conform to the clinical practice to some extent.…”
Section: Discussionmentioning
confidence: 94%
“…Thirdly, TACE and TARE were deemed as one kind of therapy in this study to establish a network, since no significant difference was reported between TACE and TARE. [23,45] Consequently, findings of the current network meta-analysis might not completely conform to the clinical practice to some extent.…”
Section: Discussionmentioning
confidence: 94%
“…There were an astonishing 26 complete responders (7.2%); 132 partial responders (38.1%); 133 patients (36.7%) with stable disease; and 58 patients (16%) had disease progression. mOS data from six studies (11,(48)(49)(50)(51)(52) showed a median of 19.6 months (4.6-32 months). One-year survival data was provided in four studies (12,47,49,51) ranging from 32 to 88.8%.…”
Section: Transarterial Chemoembolization (Tace) and Transarterial Radmentioning
confidence: 99%
“…Y-90 is the most commonly used radioembolizing product. A total of nine studies provided RECIST response data (11,(38)(39)(40)(42)(43)(44)(45)(46). There were nine complete responders (2.3%) out of the 380 total patients.…”
Section: Transarterial Chemoembolization (Tace) and Transarterial Radmentioning
confidence: 99%
See 2 more Smart Citations